(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Pharmacovigilance plays main role in ensuring drug safety by detecting, assessing, and preventing adverse drug reactions (ADRs). Healthcare professionals, like postgraduate students and clinicians, are central to ADR reporting systems. Under-reporting is a major concern inspite of positive attitude toward pharmacovigilance. Aim: To assess the knowledge, attitude, and practices (KAP) regarding pharmacovigilance and ADR reporting among postgraduate students and clinicians at a tertiary care centre. Methods: This hospital-based cross-sectional questionnaire study was done among 550 postgraduate students and clinicians at a tertiary care teaching hospital. Data were collected using a pre-validated structured questionnaire comprising sections on knowledge, attitude, and practices related to pharmacovigilance. Data were analyzed using SPSS version 17.0, and results were expressed as frequencies and percentages. Results: Among the study subjects, 78% correctly defined pharmacovigilance, and 64% were aware of the national pharmacovigilance program. 48% knew the correct procedure for ADR reporting. A positive attitude was seen among 92% who considered ADR reporting a professional responsibility and 88% acknowledged its importance in improving patient safety. 58% had seen an ADR in clinical practice. 34% had reported an ADR. Conclusion: Knowledge and attitude toward pharmacovigilance were satisfactory, but actual ADR reporting practices were suboptimal. Targeted educational interventions and regular training programs are needed to improve ADR reporting and strengthen pharmacovigilance systems.